RED FLAGS PENGELOLAAN DANA DESA - Sarinah Joyce M. Rafael; I Komang Arthana (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
The Village Fund shows a positive influence on the level of village independence, which is indicated by an increase in village status. However, it is inseparable from the various problems that arise. The task of detecting fraud is not easy. The Village Consultative Body needs indicators or signs (red flags) that can help in focusing performance when monitoring the implementation of village fund management, which can be seen in the village financial statements. This study aimsto identify the effectiveness of red flags in detecting fraud in village fund management. This research was conducted by survey method through the distribution of questionnaires to the management of village consultative bodies which acted as supervisors in village development. Data were analyzed using descriptive statistics, using a mean test to assess the effectiveness of the red flags indicator. Keywords: village funds, red flags, fraud